Total Assets Turnover Against Dividend Payout Ratio: The Role of Return On Assets Mediation - Ira Puspita Setyaningsih; Indah Yuliana (Jurnal Manajemen Indonesia, 2020)
The research objective is to examine the direct effect of TATO and ROA on the DPR, TATO on ROA, and the indirect effect of TATO on the DPR through ROA in the consumer goods industry sector in 2016-2018. The study population was all companies in the consumer goods industry sector with a total of 38 companies, while the samples taken were 21 companies. This type of research is quantitative research using Warp Partial Least Square (Warp-PLS) for data analysis. The direct effect test results show that TATO has no significant effect on the DPR, TATO significantly influences ROA and ROA significantly influences DPR. While the results of indirect influence testing prove that TATO significantly influences DPR through ROA, so the higher ROA is closer to the relationship between TATO and DPR. Keywords ? Total Assets Turnover (TATO); Return On Assets (ROA); Dividend Payout Ratio (DPR)